Enhancing ecological hierarchical problem-solving with domain-specific question agendas. Issue 17 (22nd November 2022) - Ottenhof, Koen; Westbroek, Hanna; van Muijlwijk-Koezen, Jacqueline; Meeter, Martijn; Janssen, Fred
ABSTRACT: Promoting problem-solving in students is an important aim of secondary science education. There is a mismatch, however, between the complex, ill-structured nature of realistic scientific problems, versus the well-structured problems students are generally confronted with. The current study investigates a teaching-learning strategy that resolves this mismatch by combining a focus on hierarchical problem-solving strategies for complex, authentic problems with the use of domain-specific question agendas that represent scientific perspectives . Three design principles were applied to develop an exemplary lesson series that was implemented in two Dutch pre-university classes. A pre-/post-test research design was followed in which data was collected in the form of sets of student-generated research questions. Additionally, audio recordings of lessons and student interviews were collected and analysed. Results indicate that participating students became more proficient at applying hierarchical problem-solving strategies like (1) reducing complex ecological problems to more manageable subproblems by formulating productive research questions and (2) identifying types of ecological problems by connecting them to domain-specific question agendas (problem-abstraction). A qualitative analysis of the teaching-learning process and student interviews informed potential refinements of the design principles, namely the use of more diverse contexts and a greater focus on collaborative learning.